Inflammation-Independent Antinociceptive Effects of DF2755A, a CXCR1/2 Selective Inhibitor: A New Potential Therapeutic Treatment for Peripheral Neuropathy Associated to Non-Ulcerative Interstitial Cystitis/Bladder Pain Syndrome - Brandolini, Laura; Aramini, Andrea; Bianchini, Gianluca; Ruocco, Anna; Bertini, Riccardo; Novelli, Rubina; Angelico, Patrizia; Valsecchi, Anna Elisa; Russo, Roberto; Castelli, Vanessa; Cimini, Annamaria; Allegretti, Marcello (Frontiers in Pharmacology, 2022)
Interstitial cystitis (IC)/bladder pain syndrome (BPS) is a chronic bladder disease of unknown etiology characterized by urinary frequency and episodic and chronic pain. Analgesic treatments for IC/BPS are limited, especially for patients with non-Hunner (non-ulcerative) type IC that usually have poor overall outcomes. Here, we demonstrate that oral treatment with DF2755A, a potent and selective inhibitor of chemokine receptors CXCR1/2, can prevent and reverse peripheral neuropathy associated to non-Hunner IC/BPS by directly inhibiting chemokine-induced excitation of sensory neurons. We tested DF2755A anti-nociceptive effects in a cyclophosphamide (CYP)-induced non-ulcerative IC rat model characterized by severe peripheral neuropathy in the absence of bladder inflammatory infiltrate, urothelial hyperplasia and hemorrhage. Treatment with DF2755A prevented the onset of peripheral neuropathy and reverted its development in CYP-induced IC rats, showing a strong and long-lasting anti-hyperalgesic effect. Ex vivo and in vitro studies showed that DF2755A treatment strongly inhibited the expression of the CXCR2 agonists, CXCL1/ KC and CXCL5, and of transient receptor potential vanilloid 1 (TRPV1) compared to vehicle, suggesting that its effects can be due to the inhibition of the nociceptive signaling passing through the CXCL1/CXCR1-2 axis and TRPV1. In conclusion, our results highlight the key pathophysiological role played by the CXCL1/CXCR1-2 axis and TRPV1 in the onset and development of peripheral neuropathy in non-Hunner IC and propose DF2755A as a potential therapeutic approach for the treatment of not only inflammatory painful conditions, but also of neuropathic ones, and in particular of non-Hunner IC/BPS.